(untitled) (International Research in Economics and Finance, 2017)
Economic recession has eaten deep into the economy to the extent that taxes generated cannot serve as a pivot upon which the economy could strive. This study examines how economic recession can be managed through effective tax collection. Secondary data was obtained from the CBN statistical bulletin between periods of 2003 to 2016. Regression technique was used in testing the data collected with the aid of E-VIEWS. The study revealed that taxes do not have significant positive effect on the nation’s Gross Domestic Product, Government Spending, Capacity Utilization and Money Supply. Thus, it implies that taxes in Nigeria are rather unfortunately underexploited, which is an indication of poor tax collection system. This study therefore concludes that, tax should be considered as the urgent and needful panacea to rescue the current economic illness that Nigeria is currently facing. This should be done by ensuring that relevant tax authorities have good tax collection system like effective tax data base, effective E-tax registration, effective E-tax payment and all tax payers should have tax identification number.